Amazing Escapes: Illustrated with Photographs and Prints - Gunning, Thomas G. (Dodd, Mead, 1984)
Presents nine tales of escape and survival against great odds including escapes from a great white shark, a volcanic eruption, and a fall through a thunderstorm.
Keywords: Escapes; Juvenile literature; Juvenile literature; Adventure and adventurers; Juvenile literature; Survival; dept.rdg; faculty_collection

Unexplained Mysteries - Gunning, Thomas G. (Dodd, Mead, 1983)
Describes nine strange and, as yet, unexplained events including the man who lived after spending two days inside a whale's stomach, the sighting of a dinosaur-like creature in Africa, the moving coffins of Barbados.
Keywords: Curiosities and wonders; Juvenile literature; dept.rdg; faculty_collection